Milking dairy opportunities: Youth in Kenya - International Livestock Research Institute (International Livestock Research Institute, 2020)
Can young dairy farmers make money while helping to curb greenhouse gases? How are Kenya's new generation of dairy farmers finding opportunities, and facing down challenges? Read more in the ILRI 2019 Annual Report: https://www.ilri.org/news/annual-report/kenya-meet-young-entrepreneurs-milking-opportunity-dairy-sector